(untitled) (TEL Tempo, Espaço e Linguagem, 2021)
Discusses the representations and temporalities of the sertão and sertanejo operated in Cinema Aspirinas e Urubus, a feature film of director Marcelo Gomes, released in 2005. In order to carry out these analyses, stereotypes and the experience of social relations between the characters of the film are questioned, in order to bring to the debate problems of representation and historical time. Keywords: Feature film. Sertão. Representation. Temporality.